2017
DOI: 10.1002/2017jd026997
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Aerosols and Implications for Radiative Effects in Beijing During the Asia‐Pacific Economic Cooperation Summit 2014

Abstract: An intensive measurement campaign was conducted in Beijing during the Asia‐Pacific Economic Cooperation (APEC) Summit 2014 to investigate the effectiveness of stringent emission controls on aerosol optical properties and direct radiative forcing (DRF). Average values of PM2.5, light scattering (bscat), and light absorption (babs) coefficients decreased by 40, 64, and 56%, respectively, during the APEC control period compared with noncontrol periods. For the APEC control period, the PM2.5 mass scattering and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…This should be attributed to the lower PM2.5 loadings during the NCCPC control period. The DRF reduction ratio (26.3%) during the NCCPC control period is smaller than the value during the APEC period (61.3%, Zhou et al, 2017). Furthermore, the DRF values can be as high as -24.7 and -28.2 W m -2 during the PE1 and PE2, respectively.…”
Section: Impacts Of Pm25 Emission Reduction On Aerosol Radiative Effmentioning
confidence: 76%
See 1 more Smart Citation
“…This should be attributed to the lower PM2.5 loadings during the NCCPC control period. The DRF reduction ratio (26.3%) during the NCCPC control period is smaller than the value during the APEC period (61.3%, Zhou et al, 2017). Furthermore, the DRF values can be as high as -24.7 and -28.2 W m -2 during the PE1 and PE2, respectively.…”
Section: Impacts Of Pm25 Emission Reduction On Aerosol Radiative Effmentioning
confidence: 76%
“…components to bext are found. For example, Li et al (2013) have reported that (NH4)2SO4 (41%) has the largest contribution to bext during the Olympics, followed by NH4NO3 (23%), OM (17%), and EC (9%); Zhou et al (2017) have found that OM 49%is the largest contributor to bext, followed by NH4NO3 (19%), (NH4)2SO4 (13%), and EC (12%). These differences may be attributed to the different reductions in PM2.5 chemical species and the variable RH among studies which can influence the hygroscopic properties of sulfate and nitrate.…”
Section: Impacts Of Pm25 Emission Reduction On Aerosol Radiative Effmentioning
confidence: 99%
“…In contrast, receptor models can be utilised to conduct multiple optical source apportionment of aerosol. Several studies have used a combination of the receptor model and MLR to indirectly identify sources of aerosol b scat , b abs , and b ext (Cao et al, 2012;Tian et al, 2020;Zhou et al, 2017). For example, Zhou et al (2017) first used positive matrix factorisation analysis to quantify the mass contributions of aerosol from secondary aerosol, biomass burning, trafficrelated emissions, and coal combustion based on the sole chemical species, and MLR was then used to apportion the contribution of each source to b scat and b abs .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, receptor models can be utilized to resolve multiple optical source apportionment of aerosol. Several studies used a combination of the receptor model and MLR to indirectly identify sources of aerosol b scat , b abs , and b ext (Cao et al, 2012;Tian et al, 2020;Zhou et al, 2017). For example, Zhou et al (2017) firstly used positive matrix factorization analysis to quantify the mass contributions of aerosol from secondary aerosol, biomass burning, traffic-related emissions, and coal burning based on the sole chemical species, and then the MLR was used to apportion the contribution of each source to b scat and b abs .…”
mentioning
confidence: 99%
“…Several studies used a combination of the receptor model and MLR to indirectly identify sources of aerosol b scat , b abs , and b ext (Cao et al, 2012;Tian et al, 2020;Zhou et al, 2017). For example, Zhou et al (2017) firstly used positive matrix factorization analysis to quantify the mass contributions of aerosol from secondary aerosol, biomass burning, traffic-related emissions, and coal burning based on the sole chemical species, and then the MLR was used to apportion the contribution of each source to b scat and b abs . In addition, recent studies have attempted to conduct direct optical source apportionment by combining aerosol chemical species with optical coefficients in one receptor model (Forello et al, 2019;Q.…”
mentioning
confidence: 99%